Design of event‐triggered interval functional observers for systems with input and output disturbances. (26th July 2021) - Huong, D. C.; Huynh, V. T.; Trinh, H.
Abstract : Design of event‐triggered functional observers for linear systems subject to input and output disturbances is presented in this paper. A new dynamic event‐triggered mechanism is first proposed and then a novel event‐triggered interval functional observer is designed. The designed observer provides upper and lower bounds of the unknown linear function of the state vectors. By constructing a Lyapunov function, conditions ensuring the existence of the event‐triggered functional observer are established. The smallest bound of the estimated error and an effective algorithm for determining observer matrices are also presented. Finally, the obtained results in this paper are used to estimate linear functions of the state vector of a battery and motor circuit model of electric vehicles.